Growth Performance of White Snapper (Lates calcarifer) with Different Lysine Addition in the Moving Phase - Achmad Sanjaya; Siti Hudaidah; Supriya Supriya (Jurnal Perikanan dan Kelautan, 2021)
White snapper (Lates calcarifer) is a fish that has high economic value because it has entered a large export market. The obstacle in the cultivation of white snapper is that it requires a higher protein in the threshing phase compared to larger fish to increase the growth performance of white snapper. This study aims to determine the best lysine dose for increasing the growth performance of the white snapper in the threshing phase. The research design method used was a completely randomized design (CRD) with three treatments and three replications. The treatments given were artificial feed without the addition of lysine (KPKM), artificial feed with the addition of 0,15% lysine/kg of feed (KP A), and artificial feed with the addition of lysine 0,35%/kg of feed (KP B) for 56 days. The results obtained in this study were all parameters showed that the results were not significantly different between treatments (p> 0.05) for 56 days of maintenance. This is presumed because the levels of lysine in the formulated feed and the levels of lysine absorbed by the fish in the control treatment were higher than the other treatments. Then for the survival rate, the calculation result is 100% for all treatments. Based on the results obtained, it can be concluded that there is no best lysine dose in this study